Key concepts in political geography - Gallaher, Carolyn, 1969- (London ; Los Angeles : SAGE, 2009)
Key Concepts in Political Geography is a new kind of textbook that forms part of an innovative set of companion texts for the Human Geography sub disciplines. Organized around 20 short essays, Key Concepts in Political Geography provides a cutting edge introduction to the central concepts that define contemporary research in political geography. Involving detailed and expansive discussions, the book includes: a) an introductory chapter providing a succinct overview of the recent developments in the field; b) over 20 key concept entries with comprehensive explanations, definitions and evolutions of the subject; c) extensive pedagogic features that enhance understanding including a glossary, figures, diagrams and further reading. Key Concepts in Political Geography is an ideal companion text for upper-level undergraduate and graduate students in political geography and covers the expected staples of the sub-discipline, such as nationalism, territoriality, scale, and political-economy, as well as relatively new arrivals to the field, including the other, anti-statism, gender, and post-conflict. Written by an internationally recognized set of authors, Key Concepts in Political Geography is an essential addition to any geography student's library. -- Back cover.
Pt. I. Statecraft -- Introduction / Carolyn Gallaher -- Nation-state / Mary Gilmartin -- Sovereignty / Carl T. Dahlman -- Governance / Peter Shirlow -- Democracy / Mary Gilmartin -- Pt. II. Modes of power -- Introduction / Carolyn Gallaher -- Hegemony / Carolyn Gallaher -- Territory / Carl T. Dahlman -- Geopolitics / Carl T. Dahlman -- Superpower / Carl T. Dahlman -- Pt. III. Modernity -- Introduction / Carolyn Gallaher -- Colonialism/imperialism / Mary Gilmartin -- Political economy / Carolyn Gallaher -- Ideology / Mary Gilmartin -- Socialism / Mary Gilmartin -- Neoliberalism / Carolyn Gallaher -- Globalization / Alison Mountz -- Migration / Alison Mountz -- Pt. IV. Bounding space -- Introduction / Carolyn Gallaher -- Scale / Carl T. Dahlman -- Border / Alison Mountz -- Regionalism / Carl. T. Dahlman -- Pt. V. Violence -- Introduction / Carolyn Gallaher -- Conflict / Mary Gilmartin -- Post-conflict / Carl t. Dahlman -- Terrorism / Carolyn Gallaher -- Anti-statism / Carolyn Gallaher -- Pt. VI. Identity -- Introduction / Carolyn Gallaher -- Nationalism / Alison Mountz -- Citizenship / Alison Mountz -- Postcolonialism / Mary Gilmartin -- Representation / Peter Shirlow -- Gender / Alison Mountz -- The other / Alison Mountz.
Includes bibliographical references (p. [339]-364) and index.
Keywords: Political geography